Characterization of the Verticillium dahliae Exoproteome Involves in Pathogenicity from Cotton-Containing Medium - Chen, Jie-Yin; Xiao, Hong-Li; Gui, Yue-Jing; Zhang, Dan-Dan; Li, Lei; Bao, Yu-Ming; Dai, Xiao-Feng (Frontiers in Microbiology, 2016)
Verticillium wilt, caused by the Verticillium dahliae phytopathogen, is a devastating disease affecting many economically important crops. Previous studies have shown that the exoproteome of V. dahliae plays a significant role in this pathogenic process, but the components and mechanisms that underlie this remain unclear. In this study, the exoproteome of V. dahliae was induced in a cotton-containing C’zapek-Dox (CCD) medium and quantified using the high-throughput isobaric tag technique for relative and absolute quantification (iTRAQ). Results showed that the abundance of 271 secreted proteins was affected by the CCD medium, of which 172 contain typical signal peptides generally produced by the Golgi/endoplasmic reticulum (ER). These enhanced abundance proteins were predominantly enriched in carbohydrate hydrolases; 126 were classified as carbohydrate-active (CAZymes) and almost all were significantly up-regulated in the CCD medium. Results showed that CAZymes proteins 30 and 22 participate in pectin and cellulose degradation pathways, corresponding with the transcription levels of several genes encoded plant cell wall degradation enzyme activated significantly during cotton infection. In addition, targeted deletion of two pectin lyase genes (VdPL3.1 and VdPL3.3) impaired wilt virulence to cotton. This study demonstrates that the V. dahliae exoproteome plays a crucial role in the development of symptoms of wilting and necrosis, predominantly via the pathogenic mechanisms of plant cell wall degradation as part of host plant infection.